Anger and Sadness: Gendered Emotional Responses to Climate Threats in Four Island Nations. (February 2019) - du Bray, Margaret; Wutich, Amber; Larson, Kelli L.; White, Dave D.; Brewis, Alexandra
Climate change presents an important threat to community livelihoods and well-being around the world. Biophysical vulnerability to the effects of climate change, such as sea level rise, coastal erosion, changing flora and fauna, and changing precipitation patterns are predicted to affect island nations in particular. Emotional geographies offers a theoretical entry point to understand how changing landscapes, which are often imbued with emotion and personal significance, may result in heightened emotional states and result in different outcomes depending on the severity of these changes and the biophysical vulnerability that produces them. Historically, emotion and gender have been closely linked; we use biophysical vulnerability to climate change, along with emotion and gender, to argue for a differentiated perspective on how men and women in different places may experience different emotional responses to climate change. Using a cross-cultural analysis of qualitative data from four island countries (Fiji, Cyprus, New Zealand, and the United Kingdom; total N = 272), this article explores how different sensitivities to climate change may produce differentiated emotional responses among men versus women across these four sites. Our results indicate that gender does affect the emotional response of respondents in these sites, but that local sensitivity plays an important role in differentiating these emotional responses, and their causes, between the four sites.